Veiling as Cultural Sovereignty: A Performative and Mediated Study of Rimpu in Eastern Indonesia - Hamzah, Saidin; Tajuddin, Fajri Nur; Yani, Ahmad; Khaerunnisa, Andi (LPPM IAIN Parepare, 2025)
In global discussions over Muslim women's attire, prevailing viewpoints frequently simplify modest clothing into universal classifications, neglecting its culturally distinct significances and experiential aspects across various Muslim communities. Current research on Rimpu, the traditional attire of Bimanese women in eastern Indonesia, has predominantly regarded it as a static cultural artefact, neglecting its function as a dynamic locus of social negotiation and embodied piety. This study seeks to analyse Rimpu as a symbolic and performative practice through which women in Bima navigate cultural identity, spiritual values, and social transformation in modern situations. The research utilised a qualitative ethnographic methodology in Bima Regency, employing participant observation, in-depth interviews, and documentation to capture intergenerational perspectives and daily behaviours. The data indicate that Rimpu functions in three interconnected realms: as a manifestation of cultural-religious identity, as a locus of evolving significations influenced by modernity and media, and as a commodified cultural emblem within heritage politics and visual representation. The study conceptually enhances the comprehension of Muslim women’s attire as an expression of lived Islam and performative identity, wherein piety is regionally produced, negotiated, and recontextualized rather than consistently dictated. The findings underscore the necessity to transcend mere symbolic preservation in favour of a more critical and participatory engagement with cultural practices, framing Rimpu as a perspective to reevaluate the intersections of gender, religion, and cultural transformation in the Global South